EXPLORING MERCHANT PREFERENCES IN DECISIONS TO PURCHASE PINEAPPLES FROM FARMERS IN SENURO VILLAGE - Muhammad Andri Zuliansyah; Reshi Wahyuni; Serly Novita Sari; Adli; M. Huanza; Jerry Antonio (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study was motivated by the importance of exploring traders' preferences in purchasing pineapples from farmers as an effort to strengthen the marketing chain and increase the competitiveness of local pineapple products in Senuro Village. The purpose of this study was to identify the factors that influence traders' decisions in purchasing pineapples in Senuro Village, Tanjung Batu District, Ogan Ilir Regency. This study used a survey method with a descriptive approach, involving four traders as samplings who were selected purposively. Data were collected through structured interviews using questionnaires, then analyzed descriptively and qualitatively to interpret patterns of trader preferences. The results showed five main factors that influence traders' decisions, namely quality, supply continuity, price, trust and relationships, and marketing risk. Quality is the most dominant factor because it is directly related to the fruit grading system, selling value, and market acceptance. Supply continuity is also important to maintain business stability, especially for traders who supply to markets outside the region. Price plays a secondary role after quality is met. In addition, trust between farmers and traders and the ability to manage marketing risks also influence the sustainability or strengthening of cooperative relationships.